A1.24 Shift in blood immune cell composition in ageing and osteoarthritis patients. (13th February 2015) - Ponchel, F; Burska, AN; Campbell, M; Raja, R; White, D; Emery, P; Conaghan, PG
Abstract : Background: Immuno-senescence and inflammageing are features of the ageing immune system. Such age-related abnormalities may be synergising with structural defects of the musculoskeletal system augmenting the development of OA. Our aim was to establish if abnormalities of blood immune cell composition were associated with OA, beyond defects already associated with ageing. Methods: Blood was collected from 120 healthy controls (age 18–69) to establish variations associated with age and 110 OA patients (age 49–85). Synovial tissue biopsies were obtained for 52 OA patients. We examined loss or acquisition of age-related changes in blood immune cells composition using flow-cytometry to establish frequencies of CD4/CD8, B, NK-cells. T and B-cells were analysed further for phenotypes including an inflammation related cell (IRC) subset. Immunohistochemistry was used to analyse immune cell infiltration in OA synovial tissue. Results: OA synovial tissue had a normal appearance in 13/52 samples. In 28/52 samples diffuse infiltration of T and B-cells could be observed while formation of small aggregates was found in 10 cases. The presence of an ectopic germinal centre-like structure was only seen in one sample. Lineage analysis showed no change in relation with age for NK, CD4, and B-cells, weak decline in CD8 ( rho = -0.300, p = 0.019) and increase in NKT ( rho = 0.315, p = 0.012). Phenotyping T/B-cells revealed clear age-related changes with reduction of naïve CD4 + T-cell (rho = 0.817, p < 0.0001), increased Treg (rho = 0.501, p = 0.001), increased naive B-cells (rho = -0.501, p = 0.002) and reduced memory (rho = -0.518, p = 0.002). In OA, NK cells become positively related to age ( rho = 0.350, p < 0.0001), CD4 and B-cells negatively ( rho = -0.318, p = 0.001, rho = -0.260, p = 0.006 respectively). The CD8 relationship was lost. Naïve CD4 cells appeared to be particularly affected with increased frequencies in 32/110 patients. Treg were reduced in 41/105 patients irrespective of age. IRC were only increased in 16 patients. B-cell subsets were also affected resulting in loss of age-relationships observed in health. We observed that longer disease duration was associated with loss of CD4 + T cells ( rho = -0.297, p = 0.025). IRC frequency was also associated with disease duration ( rho = 0.248, p = 0.058) and were also more frequent in patients affected in the hip (p = 0.002) or foot (p = 0.023). We observed no further association with B-cell subsets/phenotypes. Conclusion: This analysis of the immune cell composition of the blood of OA patients suggests that immune dysfunction is present in OA beyond what is directly related to ageing. The relationship to severity of OA inflammation requires further investigation. The therapeutic implications of this warrant further study.